The epidemiology of Toxocara canis and other intestinal parasites of dogs collected from Ile-Ife,Ondo,and Ede,Southwest Nigeria - Akeredolu, Adedayo Babajide (zoology,Obafemi Awolowo University, 2023)
xii, 117p